2021
DOI: 10.1016/j.fsigen.2021.102541
|View full text |Cite
|
Sign up to set email alerts
|

Determination of shedder status: A comparison of two methods involving cell counting in fingerprints and the DNA analysis of handheld tubes

Abstract: The shedder status of an individual may be important to consider in the context of DNA transfer, persistence and recovery and in Bayesian networks where a person's shedder status may have an impact on the outcome. In this study we compared two methods to determine shedder status: the handheld tube (HH) method and a fluorescent cell count (CC) method. A poor association was observed between the numbers of detected cells in a fingerprint using the CC method and the strength of the DNA result with the HH method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
(61 reference statements)
2
7
0
Order By: Relevance
“…In a study by Samie et al [15], the authors noted that the amount of DNA deposited by an individual can fluctuate greatly, and consequently, recommended to assign an individual to a shedder group based on the overall results from multiple depositions. Another study by Johannessen et al [16] attempted to use a fluorescent cell count method to determine an individual's shedder status. This method had the potential advantages of being quicker and simpler, doing away with the laborious DNA profiling processes and at the same time, eliminating variations caused by different laboratory protocols.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Samie et al [15], the authors noted that the amount of DNA deposited by an individual can fluctuate greatly, and consequently, recommended to assign an individual to a shedder group based on the overall results from multiple depositions. Another study by Johannessen et al [16] attempted to use a fluorescent cell count method to determine an individual's shedder status. This method had the potential advantages of being quicker and simpler, doing away with the laborious DNA profiling processes and at the same time, eliminating variations caused by different laboratory protocols.…”
Section: Introductionmentioning
confidence: 99%
“…However, some individuals, especially those that deposited low amounts of DNA, displayed lower variation. Individuals were classified as low, medium or high shedders based on the criteria defined by Johannessen et al [ 15 ] with the following adjustments according to the observed values of the current dataset: high shedder class was assigned to participants that had two out of three samples above the average RFU tot (62,520) and two out of three samples with 20 out of 24 full loci. Low shedder class was assigned to participants where all samples were below 8000 RFU tot and two out of three with negative or partial profiles.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been demonstrated that individuals have a different propensity to transfer DNA to handled items (shedder status); shedder status is consistent over years, and it can influence transfer probabilities [ 14 , 15 , 16 ]. However, the classification method has been debated and a need to introduce an intermediate shedder category (between high and low) has been demonstrated [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to estimate the quantity of DNA transferred in primary versus secondary transfer scenarios [ 322 ]. As quantities of DNA transferred can be highly variable and thought to be dependent on the so-called “shedder status” – how much DNA an individual exudes, several studies explored this topic [ [323] , [324] , [325] , [326] , [327] ]. Studies have also considered the level of DNA an individual transfers to untouched items in their immediate surroundings [ 328 ], the position and level of DNA transferred during digital sexual assault [ 329 ] or during various activities with worn upper garments [ 330 , 331 ], and the DNA composition on the surface of evidence bags pre- and post-exhibit examination [ 332 ].…”
Section: Advancements In Current Practicesmentioning
confidence: 99%